INTENSIFICATION GRAVITATIONAL SEDIMENTATION AND SEAL IRON CONTAINING SLUDGE IN AN ELECTRIC FIELD - and and (Municipal economy of cities. Series: «Economy science», 2013)
The research of processes of condensing and depositing of the metallurgical production sludge is executed by a gravity method using varying factors of influence – temperature, electric field.